Miskonsepsi Pembebanan Tanggung Jawab kepada Direksi Badan Usaha Milik Negara dalam Jerat Tindak Pidana Korupsi - Bayu Novendra; Aulia Mutiara Syifa (Faculty of Law, Universitas Pattimura, 2020)
The dualism of the conception of state assets separated in State-Owned Enterprises (SOEs) in Indonesian legislation raises a polemic in the operation of SOEs as a business entity. In essence, in Act Number 19 of 2003 concerning SOEs, separated state assets no longer include state assets and their development and management are based on sound corporate principles. Meanwhile, in Law Number 17 of 2003 concerning State Finance, it is stated that one of the state finances is state assets separated from SOEs. Therefore, if it is related to the enactment of Law Number 31 of 1999 concerning Eradication of Corruption, SOEs that suffer losses can be charged with criminal acts of corruption because they have harmed state finances. By using the juridical-normative method and literature study as data collection techniques, the results of this study confirm the nature of BUMN as a company that is separate from its shareholder, namely the state. This research also encourages the use of Business Judgment Rule principle in proof as an effort to protect all actions of the Directors of BUMN that have a good intention to run a BUMN that suffers losses.